Teaching Physical Education During Ramadan Observance: Practical Recommendations - Trabelsi, Khaled; Chtourou, Hamdi (International Journal of Sport Studies for Health, 2019)
Teenage students continue to participate in physical education lessons during the month of Ramadan. The combination of intermittent fasting and physical activity may result in impairment in both physical and cognitive performances. Additionally, dietary intake, sleep and hydration status may be negatively affected. To counteract the possible negative effects of intermittent fasting upon health and athletic performance of adolescent students, some practical recommendations should be outlined including (i) nutrition and sleep education of students, (ii) reducing the intensity and increasing the recovery periods during physical education lessons and (iii) practicing physical education in indoor. Additionally, teachers should be aware of clinical signs and symptoms of dehydration and hypoglycemia.